Absent mothers - Greenslade, Frances, 1961- (Demeter Press, 2017)
Missing, dead, disappeared, or otherwise absent mothers haunt us and the stories we tell ourselves. Our literature, from fairytales like Cinderella and The Little Mermaid to popular narratives like Cheryl Strayed's recent book Wild, is peopled with motherless children. The absent mother, whether in literature or life, may force us to forge an independent identity. But she can also leave a mother-shaped hole and a howling loneliness that dogs us through our adult lives. This anthology explores the theme of absent mothers from scholars and creative writers, who tell personal stories and provide.